(untitled) (NAU Journal of Library and Information Science, 2022)
Institutional repositories provide academic institutions with an opportunity to create a central location that collects and preserves their digital output. The opportunity to share and distribute this output is significant and serves to benefit the contributing authors and the institution itself. Since the purpose of an institutional repository is to make its contents freely available, then the global community also has something to gain. When an academic institution collects and shares its creative output, members of the institution not only benefit but also make the world academically richer by allowing scholarly communication to flow more freely. Academic libraries around the world are increasingly embracing institutional repositories to communicate effectively institutional scholarly output of all types. The collection, processing, preservation and integration of academic institution literature is critical to the mission of the institution, regardless of the format. Institutional repositories have enhanced wide dissemination of all types of research output globally. Institutional repository programs enhance global visibility of both the library, institution and the authors. As libraries move to support faculty digital publishing activities, the library’s relevance to the faculty and, consequently, the institution will increase.